Critical involvement of pneumolysin in production of interleukin-1 alpha and caspase-1-dependent cytokines in infection with Streptococcus pneumoniae in vitro: a novel function of pneumolysin in caspase-1 activation - Shereen Shoma; Kohsuke Tsuchiya; Ikuo Kawamura; Takamasa Nomura; Hideki Hara; Ryosuke Uchiyama; Sylvia Daim; Masao Mitsuyama (American Society for Microbiology, 2008)
Pneumolysin is a pore-forming cytolysin known as a major virulence determinant of Streptococcus pneumoniae. This protein toxin has also been shown to activate the Toll-like receptor 4 (TLR4) signaling pathway. In this study, a mutant S. pneumoniae strain deficient in pneumolysin (Δply) and a recombinant pneumolysin protein (rPLY) were constructed. Upon infection of macrophages in vitro, the ability to induce the production of interleukin-1α (IL-1α), IL-1β, and IL-18 was severely impaired in the Δply mutant, whereas there was no marked difference in the induction of tumor necrosis factor alpha (TNF-α) and IL-12p40 between the wild type and the Δply mutant of S. pneumoniae. When macrophages were stimulated with rPLY, the production of IL-1α, IL-1β, and IL-18 was strongly induced in a TLR4-dependent manner, whereas lipopolysaccharide, a canonical TLR4 agonist, hardly induced these cytokines. In contrast, lipopolysaccharide was more potent than rPLY in inducing the production of TNF-α, IL-6, and IL-12p40, the cytokines requiring no caspase activation. Activation of caspase-1 was observed in macrophages stimulated with rPLY but not in those stimulated with lipopolysaccharide, and the level of activation was higher in macrophages infected with wild-type S. pneumoniae than in those infected with the Δply mutant. These results clearly indicate that pneumolysin plays a key role in the host response to S. pneumoniae, particularly in the induction of caspase-1-dependent cytokines.